Strategies Developed to Induce, Direct, and Potentiate Bone Healing - Collignon, Anne-Margaux; Lesieur, Julie; Vacher, Christian; Chaussain, Catherine; Rochefort, Gael Y. (Frontiers in Physiology, 2017)
Bone exhibits a great ability for endogenous self-healing. Nevertheless, impaired bone regeneration and healing is on the rise due to population aging, increasing incidence of bone trauma and the clinical need for the development of alternative options to autologous bone grafts. Current strategies, including several biomolecules, cellular therapies, biomaterials and different permutations of these, are now developed to facilitate the vascularization and the engraftment of the constructs, to recreate ultimately a bone tissue with the same properties and characteristics of the native bone. In this review, we browse the existing strategies that are currently developed, using biomolecules, cells and biomaterials, to induce, direct and potentiate bone healing after injury and further discuss the biological processes associated with this repair.